MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS DAN KEPERCAYAAN DIRI SISWA MELALUI IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK - Gusti Ayu Mahayukti; Sariyasa; Ni Luh Cipta Sari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article reports the improvement of students' mathematical communication skills, students’ self-confidence, and students’ responses through the implementation of the talking stick as a cooperative learning model. Classroom action research was implemented in three cycles for class VA with a number of 26 students. Mathematical communication skills test with a description test was distributed at the end of each cycle, while the questionnaire was used to collect data on students' self-confidence and responses. The results indicated that there was an average improvement score for students' mathematical communication skills. It began with a mean score of 23.46 in the prior reflection to 76.36 in the third cycle. Likewise, students' learning outcomes have increased from 7.69% in the prior reflection and increased to 84.63% in the third cycle. The average score of students' self-confidence in the first cycle, which began with a mean score of 68.15, increased to 77.96 in the last cycle, and the student’s responses were categorized in a positive category. It indicated that the implementation of a talking stick as a cooperative learning model for elementary school students was an alternative solution to increase the students’ communication skills and self-confidence.